Determinación de la presencia de huevos de toxocara SPP en suelos del parque metropolitano el tunal de Bogotá DC (2019)
Toxacara is a nematode of the Ascaridae family with more than 30 species described, being the most clinically important for humans: Toxacara canis that infects wolves, foxes and dogs, Toxocara cati that affects cats and felines wild. (Canese, Domínguez, et al., 2003; Guarin, 2014). Human toxocariasis is one of the zoonotic diseases with the greatest report worldwide. The disease is caused by a common parasite in feces of canines, the floors of parks and sandboxes. Studies carried out in different countries from Latin America showed a prevalence in soils of public areas of 63.13% for Venezuela (2007), 54.8% in Colombia (2017), 53% in Paraguay (2003), 39% for Brazil (2005), 35.1% Argentina (2007) and 7% in Costa Rica (2007). (Guarin, 2014).